Management of the airway and lung isolation for thoracic surgery during the COVID‐19 pandemic: Recommendations for clinical practice endorsed by the Association for Cardiothoracic Anaesthesia and Critical Care and the Society for Cardiothoracic Surgery in Great Britain and Ireland. (2nd June 2020) - Thornton, M.; Reid, D.; Shelley, B.; Steven, M.
Summary: Intra‐operative aerosol‐generating procedures are arguably unavoidable in the routine provision of thoracic anaesthesia. Airway management for such patients during the COVID‐19 pandemic including tracheal intubation, lung isolation, one‐lung ventilation and flexible bronchoscopy may pose a significant risk to healthcare professionals and patients. That said, there remains a need for timely thoracic surgery for patients with lung cancer or thoracic trauma. The thoracic anaesthetic community has been confronted with the need to modify existing techniques to maximise safety for patients and healthcare professionals. With appropriate modification, aerosol generation may be mitigated against in most circumstances. We developed a set of practice‐based recommendations for airway management in thoracic surgical patients, which have been endorsed by the Association for Cardiothoracic Anaesthesia and Critical Care and the Society for Cardiothoracic Surgery in Great Britain and Ireland.